Understanding the Pathophysiology of Premature Ejaculation: Bridging the Link between Pharmacological and Psychological Interventions - Yusof, Farid; Sidi, Hatta; Das, Srijit; Midin, Marhani; Kumar, Jaya; Hatta, Muhammd H. (Current Drug Targets, 2018)
Premature ejaculation (PE) is one of the commonest male sexual dysfunctions. It is characterized by ejaculation which occurs before or soon after vaginal penetration, which causes significant psychological distress to the individual, and his partner. The exact cause of PE is still unknown but several mechanisms are proposed, and these involve complex interactions of neurophysiological, psychosocial, and cognitive factors. We discuss the role of serotonin, nitric oxide, phosphodiesterase enzymes and other neurotransmitters. Treatment of PE tends to co-occur with other sexual difficulties, especially erectile dysfunction (ED). Treatment with selective serotonin reuptake inhibitors (SSRIs) and Dapoxitene are also discussed in detail. The treatment strategy requires a comprehensive holistic approach incorporating both combination of psychopharmacological agent and cognitive-behavioral therapy (CBT). The present review highlights the integration of the hypothalamic-neural and reverberating emotional circuit and discusses the etiology and treatment for patients with PE.
Keywords: SSRIs